Entropy Analysis of Fractional Derivatives and Their Approximation - Machado, J. A. Tenreiro (2019)
Fractional derivatives (FDs) need to be calculated using series or rational fractions. The effect of such approximations are usually analysed by means of the frequency or the time responses. This paper takes advantage of a probabilistic interpretation of FDs and adopts the Shannon entropy for assessing the truncation effect produced by the approximations.